Pengaruh Green Marketing, Brand Image dan Orientasi Pelanggan terhadap Minat Beli Produk Zorlien Led yang Dimoderasikan dengan Teknologi Internet - Catarina Cori Paramitha; Nurika Haerul Utami (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2020)
This research is direct consumer buying interest in Zorlien LED products which is based on green marketing, brand image and customer orientation through technology internet consisting of 250 questionnaire respondents who have been filled out by consumers. Result of 250 respondents consisting of 17 indicators using smartpls are declared valid, because the validity test value is above the average > 0.5 and the reliability test is above the average > 0.7. Results of hypothesis testing brand image, green marketing, customer orientation and internet technology on buying interest declared significant, but when moderated the results were not significant.Keywords: Green Marketing, Brand Image, Customer Orientation and Internet Technology